2019
DOI: 10.1155/2019/1269832
|View full text |Cite|
|
Sign up to set email alerts
|

Regional Stability Analysis of Red Clay Slope Based on Different Failure Modes: A Case Study in Taizaifu Area, Fukuoka

Abstract: Red clay slopes have different failure modes in different geological and climatic contexts. Underlying weak layers are frequently witnessed in integral failures because of the reverse consolidation characteristics. On the contrary, heavy rainfall often causes superficial sliding for a considerable infiltration through developed microfractures. Based on the Geographic Information System, regional stability of red clay slopes was evaluated with two failure modes, such as “integral sliding” and “planar sliding.” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…There are several cases worldwide where slope failure due to hill cutting with taking all the precautionary measures happened worldwide and its indicated that we have to find out some other natural way to stabiles the hill slope. Ashok K Singh et al (2018) , Fang Wei (2019…”
Section: Geological and Geotechnical Assessments Of Major Landslidesmentioning
confidence: 99%
“…There are several cases worldwide where slope failure due to hill cutting with taking all the precautionary measures happened worldwide and its indicated that we have to find out some other natural way to stabiles the hill slope. Ashok K Singh et al (2018) , Fang Wei (2019…”
Section: Geological and Geotechnical Assessments Of Major Landslidesmentioning
confidence: 99%
“…Taizaifu Area, Fukuoka" [1], there was an error in the legend of Figure 11(b). e corrected figure should be as follows: e error was introduced during the production process of the article, and the publisher apologises for causing this error in the article.…”
mentioning
confidence: 99%